Validity of Law in Modern Theoretical Discourse - D. I. Lukovskaya (Теоретическая и прикладная юриспруденция)
The article examines the important, but insufficiently deeply and detailed category of “validity of law” in the legal literature. The author gives a detailed overview of interpretations of this category in the works of foreign philosophers of law (R. Alexie, R. Kauffmann etc.). As a result of the analysis, the author concludes that a combination of positivist and jusnaturalist approaches that complement each other is necessary to adequately understand the validity of the law. This provides an opportunity to build an integrative theory based on an understanding of the validity of law as an order uniting the natural and will-established beginnings.